(untitled) (Research, Society and Development, 2020)
In this ethnographic essay, we discuss the complex process of learning the academic profession, based on an example with an ethnographic observation, in which the exercise of making the familiar strange was performed in order to understand and reflect on the ways in which the processes of interaction, socialization and learning of the teaching profession within the academic institution with its routines, events, procedures, rituals etc. occur, understanding it as a community of practice. Observing the familar and reflecting on our own processes of academic and professional insertion allows us to perceive that there are instances of learning that are not restricted to the classroom space, although this is configured as a primordial space in teacher training, and, thus, allows us to value and give importance to the numerous academic events and activities that make up the teachers’ training scenario, considering that “exchanges” are recognized as learning situated as peripheral to any professional field.